Community Based Tourism for the Concept of Village Tourism Facility Development in Papan Island - Harifuddin, T; Irdinal, A (International Journal of Psychosocial Rehabilitation, 2020)
Community based tourism can create employment opportunities for local communities, and reduce poverty, where tourism income is from tourist services to tourists. In the Planning of facilities and infrastructure is needed the concept of development with the location of the local natural environment. It to be developed must be integrated. At the stage of development of tourism facilities, as natural resources and man-made resources are absolutely needed by tourists in their travels in tourist destinations, such as: roads, electricity, water, telecommunications, terminals, bridges and so forth. With the pattern of community -based tourism does not mean that people will run their own tourism business. The level of tourism implementation should be seen as part of integrated development planning that will be carried out in Papan Island of Kadoda Village Talatakoh Subdistrict of Togean Islands, which is designated as the national tourism development and the regional tourism master plan of Tojo Una-Una Regency. One of the strategies is development of marine tourism attraction in Strategic area of National Togean Archipelago, consisting of 50 national tourism destinations. The following spatial concepts that actually include many studies in planning and architecture but this process has included analysis of community-based tourism.